The Roma in Turkiye: Segregation in The Labour Market and Income Differentiations - Sinem Bağçe (Journal of Economy Culture and Society)
n labour market research, rather than demographic and human capital endowments, ethnicity is considered a major explanatory of segregation in job occupations. This article examines the role of job occupations in income differentials within the Roma in Turkiye. The sample covers 1568 respondents and represents 6445 Roma. The conventional determinants for job occupation do not work differently for the income groups. For both the poorest and richest Roma, being a worker in a regular fulltime job provides much more of an increasing effect on income than the jobs in a trade. Discrimination in the labour market is a significant explanatory for all the income groups, except the richest Roma, but it has the highest impact on the poorest Roma. Traditional job occupations do not have an impact on income differentiation within Roma, but segregation for the Roma in the labour market is clear in defining income differentiation. This article asserts that even though the job occupations of the Roma partly present a kind of continuity of the traditional professions, the Roma in Turkiye are predominantly wage earners and working for someone else rather than being self–employed. While sociocultural determinants are significant in the middle–income groups, the voting behaviour in the municipal election has decremental impacts on all the income groups of the Roma.